A participação do universitário evangélico brasileiro na Missio Dei: a propagação do evangelho para transformação da sociedade - Costa, Mauricio Jaccoud da (2013)
The young Brazilian academic has an important role in the transformation of society. The Brazilian evangelical academic, as they have a faith which touch him/her unconditionally and as they actively participate in the missio Dei contribute in an even more significant way in this transformation. This study seeks to understand the participation of Brazilian evangelical academic in the missio Dei and in the promulgation of the Gospel to transformation of society. In the first part seeks to difine the concept of missio Dei showing that this mission is a call to all people and seeks to emphasize the necessity of preaching the gospel through word and deed, believing that this preaching will lead to changes in society. The second part presents a profile of the young Brazilian evangelical academic, showing the main characteristics of Generation Y and the way young people live their religiosity. The third part analizes the young Brazilian evangelical academic in God's mission, and how it fits in the promulgation of the gospel to transform society.